The Role of CT, MRI and 3D Imaging in the Diagnosis of Temporomandibular Joint and Other Orofacial Disorders in Children - Hall Roger K. (Sciendo, 1994)
Advances in medical imaging techniques add a new third dimension (3D computer reconstruction of CT, MR and Ultrasound images) to the diagnostic armamentarium of practitioners in orofacial medicine, surgery and Orthodontics. In particular, Computerized Tomography and Magnetic Resonance lmaging with, to a lesser extent, Nuclear Medicine lmaging and Sonography provide more accurate and dctailed information on abnormalities and disorders of craniofacial osseous and soft tissues, especially the temporomandibular joint, than was previously available from plain films or tomography. Greater familiarity with these new imaging modalities by dental specialists will result in their more effective use in paediatric patients.